The Poetical Actualizationof Terms in the Literary Works - Jamoliddinova, Dilnoza (International Journal of Psychosocial Rehabilitation, 2020)
In the article the terms are scientifically proved that they are also the unit of expression. The lingvopoeticpeculiarities of the terminology used in the works of Uzbek writers are studied. Poetic actualizationof the terms is illustrated with the examples taken from the literary works.